A literature review on IoT applications in fishery cold chains: Integrating blue economy principles for sustainable food security - Harriz, Muhammad Alfathan; Setiyowati, Harlis; Akbariani, Nurhaliza Vania (Journal of Food Technology Research, 2025)
The fishery sector faces critical cold chain challenges, such as 20-30% spoilage of seafood, overfishing, illegal fishing, and information gaps. These issues threaten global food security and sustainability. This systematic literature review investigates how IoT applications enhance traceability, sustainability, and food security in fishery cold chains compared to traditional manual methods, integrating blue economy principles to promote sustainable ocean resource use. Using the PICO framework, this study examines IoT interventions (e.g., sensors, RFID, and blockchain) across capture fisheries, aquaculture, and seafood processing, with a focus on transparency, waste reduction, and alignment with SDGs 2 and 14. Following PRISMA 2020 guidelines, seven studies from 2011 to 2025 were synthesized from Scopus, Semantic Scholar, and Crossref via Publish or Perish software. MMAT appraisal rated six studies high and one medium. Findings reveal that IoT-blockchain hybrids reduce fraud by up to 35%, RFID improves real-time monitoring, and barriers such as high costs hinder adoption in developing regions. Blue economy outcomes include reduced waste, prevention of illegal fishing, and inclusive growth for SMEs. This review’s significance lies in its novel integration of IoT with blue economy principles, offering fishery-specific guidelines to advance sustainable food systems. Research gaps include scalability in the global South and AI-IoT synergies. Policymakers should prioritize IoT adoption to strengthen governance, while future studies should explore cost-effective, climate-resilient solutions.